Pengaruh Konsentrasi Urin Sapi Terhadap Pertumbuhan Dan Hasil Tanaman Caisim (Brassica juncea L.) Varietas Tosakan - Lestari, Endah; Budiasih, R; Nurhayatini, Reni; Parlinah, Linlin (OrchidAgro, 2023)
The aim of this research was to study the effect of cowurine concentration on the growth and yield of caisim (Brassica juncea L). The research was conducted in June - August 2020 in Sagalaherang Kaler Village, Sagalaherang District, Subang Regency. The experimental design used was a simple randomized block design (RBD) with 6 treatments and repeated 4 times. These treatments were: A (without cow urine), B (10 ml L-1), C (20 ml L-1), D (30 ml L-1), E (40 ml L- 1) and F (50 ml L-1). The results showed that the concentration of cow urine had an effect on the number of leaves at the age of 40 DAS and 45 DAS. Cow urine concentration of 20 ml L-1 gave the best results on the number of leaves in the Tosakan variety Caisim plant.